Assessing the Laboratory Safety and Security Skills among Science, Technology and Mathematics (STM) Teachers in Sokoto State, Nigeria - Muhammad, Rabi (American Journal of Education and Learning, 2016)
The paper, assessing the laboratory safety and security skills among science technology and mathematics (STM) teachers in Sokoto State examines STM teachers skills in the state of the art procedures and practices. Descriptive survey design was adopted for the study. A sample of ninety (90) teachers of the core science subjects was selected through stratified random sampling method from the population of science teachers in Sokoto State. Three research questions were answered. Findings of the study indicated that the science laboratories in Sokoto State lack the most essential safety devices. The study also revealed that STM teachers in Sokoto State are safety conscious but they lack the skills for good planning of laboratory activities. Based on the findings of the study, it was recommended among others that there should be effective teacher preparations and training programme that emphasizes on the acquisition of skills, and competencies as against the current system of training which is theoretically oriented.